How to expand the boundaries: feminist posthumanist elaborations on change in education - Gunnarsson, Karin (Reconceptualizing Educational Research Methodology, 2021)
Change is a vital matter connecting to key educational concerns of teaching and learning and also involves questions of ethics. By deploying a feminist posthumanist framework, this paper elaborates change together with the notions of boundaries and responsibility. This is done by exploring moments from a collaborative research project conducted in a Swedish upper secondary school concerning a teaching unit focusing on equality and norms. The questions guiding the paper are: How is change enacted within the teaching? And, how to unfold the responsibilities the teaching entails? By working within the interplay of empirical enquiry and theoretical elaboration, the paper addresses how a multitude of encounters become involved in enactments of change. Further, it unfolds how change entails both unpredictability and responsibility for teaching and learning. In the concluding notes the ambiguities of change are stressed addressing the call within posthuman ethics of how to expand the boundaries.